2018
DOI: 10.1002/cphc.201800031
|View full text |Cite
|
Sign up to set email alerts
|

QM/MM Investigation for Protonation States in a Bilin Reductase PcyA‐Biliverdin IXɑ Complex

Abstract: Herein we report quantum mechanical/molecular mechanical (QM/MM) studies to investigate the most probable protonation states of active site amino acids and bound substrate based on a recently reported neutron diffraction structure of phycocyanobilin:ferredoxin oxidoreductase (PcyA) by Unno et al. This structure was considered to be bound in its initial state of biliverdin IXα (BV), which has the C-pyrrole ring in the deprotonated state. The protonation state of BV suggested by neutron and spectroscopic studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The elucidation of the molecular origin of such small λ max shifts is not always easy from the experimental point of view and can take benefit from multiscale atomistic models rooted in theoretical chemistry: quantum mechanical (QM), molecular mechanical (MM), or hybrid QM/MM). Most of the time, the pH effect is introduced thanks to a very specific change of individual protonation states, without considering the relevance (probability) of such a chemical process at a given pH. In the present work, we will demonstrate that, indeed, the number of populated protonation states combinations ( microstates ) is always large.…”
Section: Introductionmentioning
confidence: 70%
“…The elucidation of the molecular origin of such small λ max shifts is not always easy from the experimental point of view and can take benefit from multiscale atomistic models rooted in theoretical chemistry: quantum mechanical (QM), molecular mechanical (MM), or hybrid QM/MM). Most of the time, the pH effect is introduced thanks to a very specific change of individual protonation states, without considering the relevance (probability) of such a chemical process at a given pH. In the present work, we will demonstrate that, indeed, the number of populated protonation states combinations ( microstates ) is always large.…”
Section: Introductionmentioning
confidence: 70%
“…In the WT–BV complex, H 3 O + was considered to be present between His88 and His74. However, a later computational study suggested that this interpretation may be incorrect ( 31 , 32 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, modeling it as H 3 O + and neutral His88 poses no problem for structural analysis. In the present study, the two N atoms of His88 were interpreted as protonated in I86D–BV, based on computational analysis ( 31 , 32 ).
Figure 6 A key water molecule between His74 and His88.
…”
Section: Resultsmentioning
confidence: 99%